2021
DOI: 10.3389/fpsyg.2021.658844
|View full text |Cite
|
Sign up to set email alerts
|

Do You Get What I Mean?!? The Undesirable Outcomes of (Ab)Using Paralinguistic Cues in Computer-Mediated Communication

Abstract: The shift to working from home, which has intensified due to Covid-19, increased our reliance on communication technology and the need to communicate effectively via computer-mediated communication and especially via text. Paralinguistic cues, such as repeated punctuation, are used to compensate for the lack of non-verbal cues in text-based formats. However, it is unclear whether these cues indeed bridge the potential gap between the writer’s intentions and the reader’s interpretations. A pilot study and two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…space to facilitate the legitimacy of other interests. Furthermore, defining crisis as a threat indicates efforts to normalise a significant number of victims and losses (Sobral et al, 2020;Sidi, Glikson and Cheshin, 2021;Lanza et al, 2022).…”
Section: Leadership and Impression Management During The Covid-19 Pan...mentioning
confidence: 99%
See 2 more Smart Citations
“…space to facilitate the legitimacy of other interests. Furthermore, defining crisis as a threat indicates efforts to normalise a significant number of victims and losses (Sobral et al, 2020;Sidi, Glikson and Cheshin, 2021;Lanza et al, 2022).…”
Section: Leadership and Impression Management During The Covid-19 Pan...mentioning
confidence: 99%
“…The literature asserts the significance of impression management for managing crises, including the Covid-19 pandemic Sidi, Glikson and Cheshin, 2021;Talbot and Boiral, 2021;Carnevale and Gangloff, 2022;Ono, 2022). Therefore, it is important to investigate the process in which collective meaning is created from impression management because creating meaning is at the heart of leadership in a crisis.…”
Section: Leadership and Impression Management During The Covid-19 Pan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Babii et al (2020) mentioned that number of exclamation marks may serve as as a marker for identifying emotion. A more recent study of Sidi et al (2021) examined repeated exclamation marks in a simulation, where they presented email with repeated exclamation marks and asked participants to interpret them. They concluded that females in their study tended to express their emotions using repeated punctuations more than males in their cohort (Sidi et al, 2021).…”
Section: Exclamation Marksmentioning
confidence: 99%
“…A more recent study of Sidi et al (2021) examined repeated exclamation marks in a simulation, where they presented email with repeated exclamation marks and asked participants to interpret them. They concluded that females in their study tended to express their emotions using repeated punctuations more than males in their cohort (Sidi et al, 2021). Moreover, the level of perceived sender happiness was higher for the participants who received the message with exclamation marks (Soderlund et al, 2021).…”
Section: Exclamation Marksmentioning
confidence: 99%